2011
DOI: 10.1007/s11517-011-0762-y
|View full text |Cite
|
Sign up to set email alerts
|

Another role for nitric oxide in blood flow control?

Abstract: In the current issue, Chen and co-authors present a mathematical model to simulate shear stressdependent nitric oxide (NO) transport in a small reconstructed microvascular network. Here their results are discussed in the context of NO-dependent blood flow control. Furthermore, other NO-dependent blood flow control mechanisms are briefly reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…Consistent with our result, arginine addition to the culture medium could reverse the inhibition of normal embryo development induced by NOS inhibitor (Gouge et al 1998). Nitric oxide, a product of arginine via NOS, plays an important role in blood flow control (Cornelissen 2011). Recent studies showed that arginine supplementation could increase the uterine blood flow in women and mare potentially via nitric oxide pathway ( Takasaki The ratios of uterine iNOS, eNOS, p-S6K1, and p-PKB to b-actin.…”
Section: Discussionsupporting
confidence: 87%
“…Consistent with our result, arginine addition to the culture medium could reverse the inhibition of normal embryo development induced by NOS inhibitor (Gouge et al 1998). Nitric oxide, a product of arginine via NOS, plays an important role in blood flow control (Cornelissen 2011). Recent studies showed that arginine supplementation could increase the uterine blood flow in women and mare potentially via nitric oxide pathway ( Takasaki The ratios of uterine iNOS, eNOS, p-S6K1, and p-PKB to b-actin.…”
Section: Discussionsupporting
confidence: 87%
“…We greatly appreciate the insightful editorial response written by Dr. Cornelissen [6] in reference to our paper on 3-dimensional modeling of NO transport in a microcirculatory network [5], and certainly agree with the need to include O 2 transport and reaction in future modeling efforts. Models must eventually include interactions between NO and O 2 , since: (a) O 2 is required by NO synthases (NOS) to produce NO, (b) NO reversibly inhibits tissue O 2 consumption, and (c) NO modulates blood flow and O 2 delivery through changes in smooth muscle tone.…”
mentioning
confidence: 62%